The Influence of Socio-economic, Behavioural and Environmental Factors on Taenia spp. Transmission in Western Kenya: Evidence from a Cross-Sectional Survey in Humans and Pigs. - Nicola A Wardrop; Lian F Thomas; Peter M Atkinson; William A de Glanville; Elizabeth A J Cook; C Njeri Wamae; Sarah Gabriël; Pierre Dorny; Leslie J S Harrison; Eric M Fèvre (PLoS Neglected Tropical Diseases)
Unlabelled Taenia spp. infections, particularly cysticercosis, cause considerable health impacts in endemic countries. Despite previous evidence of spatial clustering in cysticercosis and the role of environmental factors (e.g. temperature and humidity) in the survival of eggs, little research has explored these aspects of Taenia spp. Epidemiology In addition, there are significant gaps in our understanding of risk factors for infection in humans and pigs. This study aimed to assess the influence of socio-economic, behavioural and environmental variables on human and porcine cysticercosis. A cross-sectional survey for human taeniasis (T. solium and T. saginata), human cysticercosis (T. solium) and pig cysticercosis (T. solium) in 416 households in western Kenya was carried out. These data were linked to questionnaire responses and environmental datasets. Multi-level regression was used to examine the relationships between covariates and human and porcine cysticercosis. The HP10 Ag-ELISA sero-prevalence (suggestive of cysticercosis) was 6.6% for humans (95% CI 5.6%-7.7%), and 17.2% for pigs (95% CI 10.2%-26.4%). Human taeniasis prevalence, based on direct microscopic observation of Taenia spp. eggs (i.e. via microscopy results only) was 0.2% (95% CI 0.05%-0.5%). Presence of Taenia spp. antigen in both humans and pigs was significantly associated with a range of factors, including positive correlations with land cover. The presence of HP10 antigen in humans was correlated (non-linearly) with the proportion of land within a 1 km buffer that was flooding agricultural land and grassland (odds ratio [OR] = 1.09 and 0.998; p = 0.03 and 0.03 for the linear and quadratic terms respectively), gender (OR = 0.58 for males compared to females, p = 0.02), level of education (OR = 0.62 for primary level education versus no formal education, p = 0.09), use of well water for drinking (OR = 2.76 for those who use well water versus those who do not, p = 0.02) and precipitation (OR = 0.998, p = 0.02). Presence of Taenia spp. antigen in pigs was significantly correlated with gender and breeding status of the pig (OR = 10.35 for breeding sows compared to boars, p = 0.01), and the proportion of land within a 1 km buffer that was flooding agricultural land and grassland (OR = 1.04, p = 0.004). These results highlight the role of multiple socio-economic, behavioural and environmental factors in Taenia spp. transmission patterns. Environmental contamination with Taenia spp. eggs is a key issue, with landscape factors influencing presence of Taenia spp. antigens in both pigs and humans.